IL-6 and PD-L1 antibody blockade combination therapy reduces tumour progression in murine models of pancreatic cancer. Issue 2 (21st October 2016) - Mace, Thomas A; Shakya, Reena; Pitarresi, Jason R; Swanson, Benjamin; McQuinn, Christopher W; Loftus, Shannon; Nordquist, Emily; Cruz-Monserrate, Zobeida; Yu, Lianbo; Young, Gregory; Zhong, Xiaoling; Zimmers, Teresa A; et al.
Abstract : Objective: Limited efficacy of immune checkpoint inhibitors in pancreatic ductal adenocarcinoma (PDAC) has prompted investigation into combination therapy. We hypothesised that interleukin 6 (IL-6) blockade would modulate immunological features of PDAC and enhance the efficacy of anti-programmed death-1-ligand 1 (PD-L1) checkpoint inhibitor therapy. Design: Transcription profiles and IL-6 secretion from primary patient-derived pancreatic stellate cells (PSCs) were analyzed via Nanostring and immunohistochemistry, respectively. In vivo efficacy and mechanistic studies were conducted with antibodies (Abs) targeting IL-6, PD-L1, CD4 or CD8 in subcutaneous or orthotopic models using Panc02, MT5 or KPC-luc cell lines; and the aggressive, genetically engineered PDAC model (Kras LSL−G12D, Trp53 LSL−R270H, Pdx1-cre, Brca2 F/F (KPC-Brca2 mice)). Systemic and local changes in immunophenotype were measured by flow cytometry or immunohistochemical analysis. Results: PSCs (n=12) demonstrated prominent IL-6 expression, which was localised to stroma of tumours. Combined IL-6 and PD-L1 blockade elicited efficacy in mice bearing subcutaneous MT5 (p<0.02) and Panc02 tumours (p=0.046), which was accompanied by increased intratumoural effector T lymphocytes (CD62L − CD44 − ). CD8-depleting but not CD4-depleting Abs abrogated the efficacy of combined IL-6 and PD-L1 blockade in mice bearing Panc02 tumours (p=0.0016). This treatment combination also elicited significant antitumour activity in mice bearing orthotopic KPC-luc tumours and limited tumour progression in KPC-Brca2 mice (p<0.001). Histological analysis revealed increased T-cell infiltration and reduced α-smooth muscle actin cells in tumours from multiple models. Finally, IL-6 and PD-L1 blockade increased overall survival in KPC-Brca2 mice compared with isotype controls (p=0.0012). Conclusions: These preclinical results indicate that targeted inhibition of IL-6 may enhance the efficacy of anti-PD-L1 in PDAC.